Palliative Care Quality Indicators for Patients with End-Stage Liver Disease Due to Cirrhosis - Walling, A. M. (Dig Dis Sci, 2016)
BACKGROUND AND AIMS: There are guidelines for the medical management of cirrhosis and associated quality indicators (QIs), but QIs focusing on standards for palliative aspects of care are needed. METHODS: We convened a 9-member, multidisciplinary expert panel and used RAND/UCLA modified Delphi methods to develop palliative care quality indicators for patients with cirrhosis. Experts were provided with a report based on a systematic review of the literature that contained evidence concerning the proposed candidate QIs. Panelists rated QIs prior to a planned meeting using a standard 9-point RAND appropriateness scale. These ratings guided discussion during a day-long phone conference meeting, and final ratings were then provided by panel members. Final QI scores were computed and QIs with a final median score of greater than or equal to 7, and no disagreement was included in the final set. RESULTS: Among 28 candidate QIs, the panel rated 19 as valid measures of quality care. These 19 quality indicators cover care related to information and care planning (13) and supportive care (6). CONCLUSIONS: These QIs are evidence-based process measures of care that may be useful to improve the quality of palliative care. Research is needed to better understand the quality of palliative care provided to patients with cirrhosis.